2006
DOI: 10.2175/106143005x84549
|View full text |Cite
|
Sign up to set email alerts
|

Pretreatment of Sludge with Microwaves for Pathogen Destruction and Improved Anaerobic Digestion Performance

Abstract: A new way of generating Class A sludge using microwaves was evaluated through a series of laboratory‐scale experiments. Microwaves provide rapid and uniform heating throughout the material. Other benefits of microwave treatment include instant and accurate control and selective and concentrated heating on materials, such as sludge, that have a high dielectric loss factor. Sludge was irradiated with 2450‐MHz microwaves, and fecal coliforms were counted. Fecal coliforms were not detected at 65°C for primary slud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
64
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
3
3
3

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(66 citation statements)
references
References 3 publications
1
64
0
Order By: Relevance
“…Above 68°C, bacterial activity was almost ceased. Hong et al (2006) studied the application of MW treatment (specific energy 2,450 MHz and temperature 85°C) in pathogen removal in terms of fecal coliforms. They reported that Class A sludge can be produced constantly with continuously fed mesophilic anaerobic digester using MW pretreated sludge at 65°C.…”
Section: Mw Irradiationmentioning
confidence: 99%
“…Above 68°C, bacterial activity was almost ceased. Hong et al (2006) studied the application of MW treatment (specific energy 2,450 MHz and temperature 85°C) in pathogen removal in terms of fecal coliforms. They reported that Class A sludge can be produced constantly with continuously fed mesophilic anaerobic digester using MW pretreated sludge at 65°C.…”
Section: Mw Irradiationmentioning
confidence: 99%
“…Moreover, both DNA and bacterial cellular membranes can be damaged by microwave irradiation. Such an effect on the treatment process, besides heating, is referred to as the athermal effect (Hong et al 2006). Microwave heating has been applied in various processes and manufacturing industries, such as food process, wood drying and waste treatment process (Jones, et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Microwave heating has been applied in various processes and manufacturing industries, such as food process, wood drying and waste treatment process (Jones, et al, 2002). For the sewage wastewater treatment industry, there are many applications of microwave heating on sludge treatment for reducing volume, improving dewaterability, enhancing digestibility, enhancing nutrient release, pathogen destruction, and stabilizing heavy metal (Menendez, et al, 2002;Liao, et al, 2005;Wojciechowaska 2005;Hong et al, 2006;Eskicioglu et al, 2007;Hsieh et al, 2007;Yu, et al, 2010). It has also been reported that the overall treatment efficiency could be increased with a combination of microwave heating with chemicals (thermo-chemical) for the treatment of sludge (Chan, et al, 2007;Qiao, et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Microwave radiation can lead to a combination of thermal and non-thermal effects on cell disruption, and possible release of cellular organic matter [40,41]. Intracellular liquid heating to boiling point leads to the thermal effect, increasing kinetic energy as molecular rotation [42], while the non-thermal effect causes the disruption of hydrogen bonds due to the polarisation of macromolecule chains aligning with electromagnetic poles [43]. The addition of hydrogen peroxide and acids during this treatment can further help solubilize WAS solids, and release ammonia and phosphorus.…”
Section: Short-chain Fatty Acidsmentioning
confidence: 99%